Safety and efficacy of a feed additive consisting of lasalocid A sodium and nicarbazin (Nilablend™ 200G) for chickens for fattening (Zoetis Belgium SA). (22nd March 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the coccidiostat Nilablend™ 200G containing lasalocid A sodium and nicarbazin. Nilablend™ 200G is not safe for chickens for fattening at the proposed maximum use level of 50 mg lasalocid A sodium + 50 mg nicarbazin/kg complete feed. Concurrent administration of Nilablend™ 200G (containing lasalocid A sodium) with tiamulin and certain other medicinal substances should be avoided. Lasalocid A sodium has antimicrobial activity against Gram‐positive bacterial species while many Enterobacteriaceae are naturally resistant. Induction of resistance and/or cross‐resistance was not observed in experimental conditions. No information on the interactions of nicarbazin with feed materials, other approved additives or medicinal products have been provided. No data were submitted on the microbiological safety of nicarbazin. The toxicological package for lasalocid A sodium and nicarbazin identified no observed adverse effect levels (NOAELs) that could be the basis for setting health‐based guidance values (e.g. an acceptable daily intake (ADI)). The Panel concluded that a concern for the genotoxicity of nicarbazin in Nilablend™ 200G cannot be excluded and that clarification on the mechanism of action of the test items would be needed. Therefore, the FEEDAP Panel is not in the position to establish an ADI for DNC on which to base the assessment of consumer safety. Nilablend™ 200G is considered toxic by inhalation, corrosive and irritant to eyes, slightly irritant to the skin but not a skin sensitiser. Inhalation exposure is considered a risk to persons handling the additive. The FEEDAP Panel cannot conclude on the safety of Nilablend™ 200G for the environment due to a possible risk for aquatic compartment (freshwater) for DNC. The efficacy of Nilablend ® 200G was demonstrated.